Recurring Critical Issues of Student Counsellors - Morrissette, Patrick J. (Canadian Journal of Counselling and Psychotherapy, 1996)
This paper describes personal, clinical and supervisory based issues that tend to emerge duringthe training process of master's level and doctoral level counselling psychology students. Theintention of this paper is to augment the available counsellor development literature andprovide information upon which to launch future research and curriculum developmentdesign.